Оло зэм, оло даур (Удмуртия, 2008)
Экземпляры: Селтинская детская библиотека (20101117) / Инвентарный номер: 229 / Цена: 150.00 / Сис.шифр: 82.3(2Рос=Удм) / Авт.знак: О 55 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм)